Assessment of total ecotourism resources of Bangkunthian mangrove forest, Thailand - Kerati Sawangwongtham; Tsusaka, Takuji W.; Faysse, Nicolas; Kim, Sohee Minsun; Royal Thai Government Fellowship (Pathum Thani : Asian Institute of Technology, 2019)
Mangrove forests are one of the natural resources which provide many benefits to humans. However, mangrove forests around the world are faced with degeneration and resource reduction. Economic valuation of mangrove forests provides values of mangrove forests in monetary terms, which helps emphasize the values of mangrove forest to stakeholders. While the choice of valuation methods depends on the type of goods and services generated by mangrove forests, this research will conduct valuation of the ecotourism resources of Bangkunthian mangrove forest, the only one mangrove forest in Bangkok area by using the contingent valuation method in term ofTEV. The results were collecting by using questionnaires which were collected from tourists who visited the mangrove forests in February 2019. TEV of Bangkunthian mangrove forests is 601,939 US$ (19,192,266 THB)l a year. It is from use value is 519,818 US$ (16,573,920 THB) per year, option value is 42,311 US$ or (1,349,040 THB) in a year and existence value 39,810 US$ (1,269,306 THB) per year. The variables which influenced use value are education, income and expense. The variables which influenced option value are education, male member ratio in household and knowing ecotourism. For existence value, affected variables are income of household, education level and knowing in ecotourism. The results of this research can be used as guideline to relevant organizations in the mangrove forests management. The results in economic values can be help for set up entrance fee and donation. Moreover, the results can also help in the mangrove forests improvement in facilities and services.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Natural Resources Management, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2019
Keywords: Ecotourism -- Thailand -- Bangkunthian Mangrove; Ecosystem services -- Thailand -- Bangkunthian Mangrove; Mangrove forests -- Economic aspectszThailand -- Bangkunthian Mangrove